The Role of Capital Expenditures, Human Development Index and Access to Electricity on Economic Growth in Java and Non-Java Islands - Rizky Oktabriani Putri (MediaTrend, 2021)
This study aims to determine whether there is a positive effect of capital expenditure, HDI and access to electricity on economic growth and is there a difference between economic growth in Java (in fact as a development area) and the Non-Java region. The data source used is secondary data in the form of the 2015 Ministry of Finance Report, as well as the publication of the Central Statistics Agency. The analysis used is the Ordinary Least Square (OLS) analysis where this test was carried out in 33 provinces in Indonesia (North Kalimantan was not used in the observation because it was a newly formed province). From the test results, it is found that: Capital Expenditure, HDI has a positive and significant effect on Economic Growth. Meanwhile, Electricity Accessibility has no influence on growth. This condition means that the economic growth in the Java Region is indeed higher than the economic growth outside Java.